Segment-specific prevalence of carotid artery plaque and stenosis in middle-aged adults and elders in Taiwan: A community-based study - Chao-Liang Chou; Yih-Jer Wu; Chung-Lieh Hung; Chun-Chieh Liu; Shwun-De Wang; Tzu-Wei Wu; Li-Yu Wang; Hung-I. Yeh (Journal of the Formosan Medical Association, 2019)
Background: Plaque in carotid arteries (CAs) is a major factor of systemic atherosclerosis and cardiovascular disease (CVD). The left and right CAs have different anatomic and geometric features and may influence the predictability of CVD. However, the site- and segment-specific prevalence of carotid plaques (CP) and study on severity of carotid atherosclerosis with CVD risks was very limited. Methods: We enrolled 1539 healthy residents aged 40-to-74 years from two northern districts in Taiwan. All volunteers received high resolution B-mode carotid ultrasound scans and CVD risk factors evaluations. Results: The prevalence rate of extracranial CP was 21.9% in females and 33.8% in males. Carotid bifurcation is the most affected segment. As compared with the right CAs, the age-sex-adjusted matched odds ratio of having plaques in the left CAs was 1.32 (95% confidence interval = 1.02–1.73). The proportions of subjects had a total plaque number≥2, maximum stenosis≥30%, and plaque score≥3 were 8.9, 10.3, and 7.2%, respectively, in females and were 17.7, 17.2, and 15.1%, respectively, in males. Among subjects with moderate and severe carotid atherosclerosis, the mean ± SD of estimated 10-year CVD risk was 19.1 ± 14.6% and more than 65% of them need intensive blood pressure, lipids, or sugar controls. Conclusion: We found that bifurcation was the most prevalent segment, and left CAs was more likely to form plaque than right CAs. The major CVD risk factors were highly prevalent and the estimated CVD risks were high in subjects with more advanced carotid atherosclerosis. The study provides further direction for CVD prevention and treatment. Keywords: Carotid plaque, Segment-specific, Cardiovascular risk factors, Community-based study